2016
DOI: 10.1108/he-03-2014-0045
|View full text |Cite
|
Sign up to set email alerts
|

An examination of Health Promoting Schools in Ireland

Abstract: Purpose: This paper reports the results of a national survey that examined the extent of implementation of health promoting schools (HPS) in Ireland.Design/methodology/approach: A quantitative research design was adopted. A questionnaire was administered to all post primary schools in the country (n=704). Data were analysed with the support of the software packages, SPSS and MaxQDA.Findings: A response rate of 56% (n=394) was achieved. Over half of these schools (56%) selfidentified as health promoting. School… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 31 publications
(39 reference statements)
1
37
1
Order By: Relevance
“…Schools have immense potential as an arena for health promotion (WHO, 1999) and the increasing emphasis on wellbeing as an area of learning and a basis for school self-evaluation is likely to enhance this role. Previous research (see, for example, Nic Gabhainn et al, 2010;Moynihan et al, 2016) has suggested challenges in adopting whole-school approaches to health promotion, with teacher professional development emerging as a key factor. Nonetheless, measures to promote school engagement and promote a more positive school climate are likely to have positive spill-overs for health behaviour.…”
Section: Implications For Policymentioning
confidence: 99%
“…Schools have immense potential as an arena for health promotion (WHO, 1999) and the increasing emphasis on wellbeing as an area of learning and a basis for school self-evaluation is likely to enhance this role. Previous research (see, for example, Nic Gabhainn et al, 2010;Moynihan et al, 2016) has suggested challenges in adopting whole-school approaches to health promotion, with teacher professional development emerging as a key factor. Nonetheless, measures to promote school engagement and promote a more positive school climate are likely to have positive spill-overs for health behaviour.…”
Section: Implications For Policymentioning
confidence: 99%
“…Similar issues were pointed out in the Irish research -the respondents there outlined a range of individual themes implemented in schools such as substance use, anti-bullying, healthy eating, but the existence of a coherent HPS policy under which these themes could be addressed was lacking. Parents were visible in only 2% of the responses concerning school activities and descriptions of more meaningful partnerships with the local community were limited and were clearly an area requiring more support (Moynihan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For more eff ective implementation of health promotion from the whole school perspective, national educational policies need to conceptualise the whole school approach more clearly. Taking into consideration the diversity of health promotion practices among schools, outlining specifi c indicators for each HPS component would be helpful (Moynihan et al, 2016). Moreover, schools need strong organizational and material support in their endeavours to become health promoting schools.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also numbers of papers analysing the data from the HKHSA as comprehensive system of monitoring and evaluation of performance of HPS [24][25][26][27][28]. Cochrane Review of WHO HPS framework for improving the health and well-being of students and their academic achievement has been conducted [29].…”
Section: Healthy School Award Scheme To Establish High Quality Standamentioning
confidence: 99%